IMPLEMENTATION OF 3D DIORAMA MEDIA BASED ON PjBL MODEL TO IMPROVE STUDENTS' CREATIVE THINKING ABILITIES IN GEOGRAPHY LEARNING - Silvi Putri; Nofrion (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Students' creative thinking skills in Geography subjects are still not optimal. This is reflected in the lack of students' ability to generate new ideas, provide alternative solutions to geographical problems, and limited ability to analyze geographical phenomena in depth. The study aimed to determine how much influence the application of 3D diorama media based on the project-based learning (PjBL) model has on improving students' creative thinking skills in geography subjects at SMAN 1 Padang Panjang. The type of quantitative quasi-experimental research comes from the development of actual experiments. The total research population of Phase E SMAN 1 Padang Panjang students in the 2024/2025 Academic Year. The sample determination method used in this study was the purposive sampling technique. The research sample of Phase E class X.9 consisted of 36 students used as the experimental class, and Phase E class X.6 consisted of 36 students used as the control class. Data collection techniques were observation, documentation, and testing. The data obtained from this study were processed with the help of IBM SPSS for the T and N-gain tests. The results of the study revealed that the application of 3D Diorama media based on Project Based Learning (PjBL) Model has a positive and significant effect on students' creative thinking skills in geography subjects at SMAN 1 Padang Panjang in the practical category with an average overall percentage reaching 71.72% in the reasonably creative and the results of the N-Gain test with a value of 65.996% in the reasonably practical category. This shows that the 3D Diorama Media Based on Project Based Learning (PjBL) Model is more effective in improving creative thinking and student learning outcomes than conventional learning models.